How to lose a guy in 10 days - McConaughey, Matthew; Hudson, Kate, 1979-; Alexander, Michelle; Long, Jeannie; Petrie, Donald (Hollywood, Calif. : Paramount, 2003)
A "How to" columnist for a trendy magazine agrees to write a first-hand account about what it takes to drive a man out of a woman's life--in exactly 10 days.
Based upon the book by Michele Alexander and Jeannie Long.
Special features: director's commentary, mapping out the perfect movie, deleted scenes, mapping out the perfect location, music video.
Director of photography, John Bailey ; music, David Newman ; screenplay, Kristen Buckley, Brian Regan, Burr Steers.
Matthew McConaughey, Kate Hudson ... [et al.].
DVD.
In English; also dubbed into French; optional English subtitles.
Keywords: Man-woman relationships -- Drama; Dating (Social customs) -- Drama; Comedy films; Video recordings for the hearing impaired; Feature films